VALOR AGREGADO AOS ESTUDANTES NOS CURSOS DE ADMINISTRAÇÃO: UMA COMPARAÇÃO DO DESEMPENHO ENTRE INSTITUIÇÕES DE ENSINO SUPERIOR PÚBLICAS E PRIVADAS - Adriana Amadeu Garcia (Universidade Federal de Santa Catarina, 2014)
The aim of this article is to analyze undergraduate management schools performances in Brazil. IDD was used as an indicator capable of measuring added value to the students based on the difference between their observed and expected performances. The research used database published by INEP – a government institution in charge of testing Brazilian students. Results showed that the IDD brings equality to the evaluation process of undergraduate courses and demonstrated that, avoid to common sense, public undergraduate business courses are not the better and private courses don’t add more value to the students.